The Potential Impact of the Orexinergic System on the Symptoms of Coronavirus-Infected Patients - Haddad, Muhammad; Khazali, Homayoun; Janahmadi, Mahyar (Novelty in Biomedicine, 2021)
Coronavirus disease in 2019 (COVID-19) is a pandemic declared by the World Health Organization after its appearance in the Chinese city of Wuhan in late 2019. It has infected more than 30 million people worldwide and led to the death of nearly one million of them. Orexin-A (OXA), a neuropeptide produced by the lateral hypothalamic area and several peripheral tissues, regulates appetite, reproduction, and other physiological functions. There are many symptoms associated with infection with the coronavirus, such as a cytokine storm, narcolepsy, impaired senses of smell and taste, and loss of appetite, usually are associated with high or low levels of OXA in the infected people. Moreover, some chronic diseases such as cancer, diabetes, and obesity, generally referred to as risk factors for the disease, increase the severity of infection or even lead to death and they are associated with either an increase or a decrease in OXA levels. Moreover, some factors, such as a high testosterone level, facilitate the entry of a virus into the cells, which OXA controls. In this review, we described for the first time the potential impact of high or low levels of OXA on the severity of the symptoms of COVID-19 or the death due to this disease.